1992
DOI: 10.1148/radiology.185.3.1438767
|View full text |Cite
|
Sign up to set email alerts
|

Arterial and venous blood flow: noninvasive quantitation with MR imaging.

Abstract: Quantitative measurements of arterial and venous blood flow were obtained with phase-contrast cine magnetic resonance (MR) imaging and compared with such measurements obtained by means of implanted ultrasound (US) blood flow probes in anesthetized dogs. The US flowmeter was enabled during a portion of each MR imaging sequence to allow virtually simultaneous data acquisition with the two techniques. MR imaging data were gated by means of electrocardiography and divided into 16 phases per cardiac cycle. The rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(77 citation statements)
references
References 0 publications
1
76
0
Order By: Relevance
“…In contrast to the mechanical energy balance approach, the calculation of the VD does not require any pressure data; only the three spatial components of the fluid velocity vector are necessary. Magnetic resonance (MR) phase velocity mapping (PVM) [22] is currently the only established clinical technique to measure all three spatial components of the velocity vector in every volume element of an imaging slice, showing high in vitro and in vivo accuracy and precision [23][24][25][26][27][28][29][30][31][32][33][34]. The advantage of MR PVM to measure the three-directional blood velocity has enabled the generation of velocity vector maps in vitro and in vivo, showing (qualitatively) the fluid mechanical superiority of the TCPC over other connections and the importance of the presence of caval offset and flaring at the connection site [14,15,[33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the mechanical energy balance approach, the calculation of the VD does not require any pressure data; only the three spatial components of the fluid velocity vector are necessary. Magnetic resonance (MR) phase velocity mapping (PVM) [22] is currently the only established clinical technique to measure all three spatial components of the velocity vector in every volume element of an imaging slice, showing high in vitro and in vivo accuracy and precision [23][24][25][26][27][28][29][30][31][32][33][34]. The advantage of MR PVM to measure the three-directional blood velocity has enabled the generation of velocity vector maps in vitro and in vivo, showing (qualitatively) the fluid mechanical superiority of the TCPC over other connections and the importance of the presence of caval offset and flaring at the connection site [14,15,[33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Phase contrast (PC) MRI to quantify blood flow velocities has been validated in several studies (1)(2)(3). Most human applications focus on large vessels such as the aorta, carotids, or femoral arteries.…”
mentioning
confidence: 99%
“…There are several limitations to our study, one of which is that the blood volume flow rate was not confirmed by methods other than phase-contrast MRI. However, the accuracy of cine phase-contrast MRI for blood volume measurement was proven in animal studies (11,12) and we believe that the blood volume flow rates measured by cine phase-contrast MRI can be used as the gold standard.…”
Section: Discussionmentioning
confidence: 97%